2021
DOI: 10.17532/jhsci.2021.1229
|View full text |Cite
|
Sign up to set email alerts
|

The effect of Benson relaxation technique on fatigue of patients diagnosed with multiple sclerosis

Abstract: Introduction: The previous studies showed that fatigue is a very common symptom in patients diagnosed with multiple sclerosis (MS) and has the greatest effect on their activities of daily living. Benson relaxation technique (BRT) is one of the most relaxation techniques used to decrease fatigue, improve emotional status and quality of life in patients with several chronic diseases. This study aimed to investigate the effect of BRT on fatigue level of patients diagnosed with MS in Jordan.Methods: This is a quas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 34 publications
(42 reference statements)
0
2
0
Order By: Relevance
“…The Benson method of relaxing functions from the mind to the muscles. Benson relaxation focuses on certain words or phrases that are repeated in a regular rhythm and are accompanied by an attitude of submission to God Almighty, who will offer a response or stimulus in relaxing the heart, thereby causing the entire body to relax (Safitri et al, 2018;Alzaghmouri et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…The Benson method of relaxing functions from the mind to the muscles. Benson relaxation focuses on certain words or phrases that are repeated in a regular rhythm and are accompanied by an attitude of submission to God Almighty, who will offer a response or stimulus in relaxing the heart, thereby causing the entire body to relax (Safitri et al, 2018;Alzaghmouri et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that BRT has positive effects on fatigue, QOL, sleep quality, pain, anxiety, and stress among different populations. [25][26][27][28] Among patients with HF, only 1 randomized controlled trial examined the effect of BRT on fatigue. 20 This study showed that BRT was effective in reducing fatigue levels.…”
Section: Introductionmentioning
confidence: 99%
“…20 Among other populations, it has been shown that BRT can positively affect the daily activity of patients undergoing hemodialysis and was used as a complementary treatment to reduce fatigue in multiple sclerosis patients. [28][29][30] Moreover, BRT was found to improve quality of sleep for patients after open heart surgery, 31 and decrease intensity of postoperative spinal anesthesia pain. 32 However, this technique has not been well tested on fatigue and QOL among patients diagnosed with HF.…”
Section: Introductionmentioning
confidence: 99%
“…[19],This study aimed to investigate the effect of BRT on fatigue level of patients diagnosed with MS in Jordan patients after BRT intervention showed significant improvement in overall fatigue level. Benson's Relaxation Technique, which involves deep breathing, muscle relaxation, and focusing on a calming word or phrase, may impact fatigue through several physiological mechanisms -Stress can exacerbate fatigue by activating the sympathetic nervous system and releasing stress hormones like cortisol.…”
mentioning
confidence: 99%